Assessment of the water quality parameters in relation to fish community of Osinmo reservoir, Ejigbo, Osun State, Nigeria - KOMOLAFE, O.O; ADEDEJI, A.A; FADAIRO, B (Research Gate, 2020)
International Journal of Biological and Chemical Sciences, VOL. 8, NO. 2, P.596-609